Antimicrobial stewardship: attempting to preserve a strategic resource - Trevor Van Schooneveld, Md (Greater Baltimore Medical Center, 2011)
Antimicrobials hold a unique place in our drug armamentarium. Unfortunately the increase in resistance among both gram-positive and gram-negative pathogens coupled with a lack of new antimicrobial agents is threatening our ability to treat infections. Antimicrobial use is the driving force behind this rise in resistance and much of this use is suboptimal. Antimicrobial stewardship programs (ASP) have been advocated as a strategy to improve antimicrobial use. The goals of ASP are to improve patient outcomes while minimizing toxicity and selection for resistant strains by assisting in the selection of the correct agent, right dose, and best duration. Two major strategies for ASP exist: restriction/pre-authorization that controls use at the time of ordering and audit and feedback that reviews ordered antimicrobials and makes suggestions for improvement. Both strategies have some limitations, but have been effective at achieving stewardship goals. Other supplemental strategies such as education, clinical prediction rules, biomarkers, clinical decision support software, and institutional guidelines have been effective at improving antimicrobial use. The most effective antimicrobial stewardship programs have employed multiple strategies to impact antimicrobial use. Using these strategies stewardship programs have been able to decrease antimicrobial use, the spread of resistant pathogens, the incidence of C. difficile infection, pharmacy costs, and improved patient outcomes.